Decibel: Isolation and Sharing in Disaggregated Rack-Scale Storage - Nanavati, Mihir; Wires, Jake; Warfield, Andrew (NSDI '17, 2017)
The performance characteristics of modern non-volatile storage devices have led to storage becoming a shared, rack-scale resource. System designers have an imperative to rethink existing storage abstractions in light of this development. This paper proposes a lightweight storage abstraction that encapsulates full-system hardware resources and focuses only on isolating and sharing storage devices across multiple, remote tenants. In support of this, it prototypes a shared-nothing runtime capable of managing hardware and scheduling this abstraction in a manner that avoids performance interference and preserves the performance of the storage devices for tenants.